D Allele and DD Genotype of I /D Polymorphism in The ACE Gene in Patients with Hypertension, Stroke And Cancer Prostate In Libreville: A Concern Given The High Frequencies of these Signatures in Gabonese Population - Ollomo Benjamin; Yacka Mouélé Laurianne; Bivigou-Mboumba Berthold; Mve Ondo Bertrand; Lendoye Elisabeth; Mezui Jerome; Mbang Mboro Thélesfort; Ndjila Céleste; Emmanuel Ecke Nzengue Jean; Makandja Roger; kouna Philomène; Ngou Milama Edouard (Journal of Proteomics and Genomics Research, 2019)
Background During the last two decades, the polymorphism of Angiotensin-Converting Enzyme (ACE) gene has been extensively studied among different human populations. In humans, several studies have shown the relationship between this polymorphism and the risk of many serious diseases with a heavy burden of health in developing countries. After analyzing the polymorphism in the population, the present study was also concerned with the investigation of an eventual association between hypertension, stroke, cancer prostate and I/D polymorphism of the ACE gene. Materials and Methods Our study population included 163 Baka (pygmy) and 158 Fang (Bantu) from Gabon to evaluate the polymorphism in the country. Concerning the diseases, we included 105 patients and 120 controls for hypertension, 37 patients stroke matched with 50 controls and 97 patients with prostate cancer were recruited. All participants in the study were genotyped for the ACE I/D polymorphism obtained by polymerase chain reaction amplification on genomic DNA. Results Our analysis showed that the ACE D allele DD genotype frequencies were highest of all the data so far in human populations. We obtained a frequency of 0.138 for I allele and 0.862 for D allele among pygmy and the frequencies of 0.313 and 0.687 respectively for the I and D alleles. This difference was significant (p<0.05). In patients, we revealed the predominance of D allele and DD genotype for hypertension (0.27 for I allele and 0.73 for D allele), for stroke (0.15 for I allele and 0.85 for D allele) and 83% of individuals with cancer prostate carry the D allele. D allele and DD genotype are associated with risk to hypertension whereas allele I seem protective at the occurrence of stroke (p<0.05 between healthy and controls). Conclusion We show that the D allele and DD genotype were higher in this population. Also theses two signatures may be associated at genetic risk of hypertension, stroke and prostate cancer in this country deprived of human resources for quality care of many patients.